2008
DOI: 10.1163/156856808786451453
|View full text |Cite
|
Sign up to set email alerts
|

Binocular disparity only comes into play when everything else fails; a finding with broader implications than one might suppose

Abstract: This paper calls attention to research showing that binocular disparity, which is an effective cue to depth, plays a secondary role, at best, in the perception of 3D shape. This claim has implications both for how shape should be studied and how this unique perceptual property should be modeled. These issues are discussed from a historical perspective, which shows how the failure to appreciate the importance of the Gestalt grouping principle called 'Figure-Ground Organization' led to many unfruitful efforts. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
1
11
2
Order By: Relevance
“…In our study, the stereo parallax signals were stronger than the motion parallax signals; it is possible that, if we degraded the stereo information by adding noise, the motion parallax could have improved the recovery of 3D shape under binocular viewing. Although previous researchers have argued that stereo parallax plays a secondary role in 3-D shape perception (Pizlo et al, 2005(Pizlo et al, , 2008(Pizlo et al, , 2010, we find that observers performed best under binocular viewing. Pizlo et al (2005Pizlo et al ( , 2008 have re-introduced the concept of an abstract 3-D shape as separate from the physical object itself.…”
Section: Discussioncontrasting
confidence: 92%
“…In our study, the stereo parallax signals were stronger than the motion parallax signals; it is possible that, if we degraded the stereo information by adding noise, the motion parallax could have improved the recovery of 3D shape under binocular viewing. Although previous researchers have argued that stereo parallax plays a secondary role in 3-D shape perception (Pizlo et al, 2005(Pizlo et al, , 2008(Pizlo et al, , 2010, we find that observers performed best under binocular viewing. Pizlo et al (2005Pizlo et al ( , 2008 have re-introduced the concept of an abstract 3-D shape as separate from the physical object itself.…”
Section: Discussioncontrasting
confidence: 92%
“…The result would be a pitting of the evidence of depth from disparity and the contrary evidence from perspective. Indeed, in naturalistic viewing conditions, with the availability of multiple cues to depth, the contribution of stereo information in the recovery of 3-D shape may be low [46]. Hence, symmetry in depth might be most effectively judged by cues other than, or in addition to, disparity-an additional source of task difficulty in the present experiments.…”
Section: On Task Difficultymentioning
confidence: 77%
“…Rather than attempt evaluation of near-threshold disparities, for instance, a quick-and-dirty decision about relative distance from the observer may be made on the basis of familiarity with an object (Ittelson, 1951) or likely object shape (Pizlo, Li & Steinman, 2008). It has recently been shown that the visual system can learn new long-term biases, when presented with new environmental contingencies: Through an associative learning paradigm, the perceived direction of rotation of a perceptually bistable wire-frame (Necker) cube at stimulus onset becomes dependent on its retinal location (Haijiang et al, 2006; Harrison & Backus, 2010a).…”
Section: Introductionmentioning
confidence: 99%